Empirical model representing microbial activity in a submerged MBR treating strength wastewater - Hasar, H; Kinaci, C (Elsevier Science Bv, 2004)
An expression for representing the microbial activity of biomass in the submerged membrane bioreactor treating whey was developed by considering the ratio of inert chemical oxygen demand (COD) in the effluent to that in the influent (C-s/C-0) and the ratio of volatile suspended solids to the suspended solids (MLVSS/MLSS). Subsequently, two expressions for the effects of above parameters on the specific oxygen uptake rate were statistically determined using a mathematical model developed by the regression analysis technique, including either the power function or the exponential growth models.
Keywords: submerged membrane bioreactor; viability; multi-regression analysis